2014
DOI: 10.1021/mp500005v
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Protein Aggregation during Storage in Lyophilized Solids Using Solid State Amide Hydrogen/Deuterium Exchange with Mass Spectrometric Analysis (ssHDX-MS)

Abstract: Solid state amide hydrogen/deuterium exchange with mass spectrometric analysis (ssHDX-MS) was used to assess the conformation of myoglobin (Mb) in lyophilized formulations, and the results correlated with the extent of aggregation during storage. Mb was colyophilized with sucrose (1:1 or 1:8 w/w), mannitol (1:1 w/w), or NaCl (1:1 w/w) or in the absence of excipients. Immediately after lyophilization, samples of each formulation were analyzed by ssHDX-MS and Fourier transform infrared spectroscopy (FTIR) to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 49 publications
9
67
0
Order By: Relevance
“…ssHDX-MS is able to distinguish the effects of different formulation excipients on structure in lyophilized solids 15,16 , and, in a recent study of lyophilized myoglobin formulations, provided significantly higher correlation with aggregation during storage than FTIR 17 . ssHDX-MS is not without its limitations, however.…”
Section: Introductionmentioning
confidence: 99%
“…ssHDX-MS is able to distinguish the effects of different formulation excipients on structure in lyophilized solids 15,16 , and, in a recent study of lyophilized myoglobin formulations, provided significantly higher correlation with aggregation during storage than FTIR 17 . ssHDX-MS is not without its limitations, however.…”
Section: Introductionmentioning
confidence: 99%
“…Previous ssHDX-MS studies in our lab have shown a correlation between deuterium incorporation in freshly lyophilized samples and aggregation during storage over a year, with greater stability for formulations showing lower deuterium incorporation 29 . It is reasonable to expect a similar correlation for process-induced differences in ssHDX-MS, though extended storage stability studies were not conducted here.…”
Section: Discussionmentioning
confidence: 70%
“…FTIR spectra were acquired for all lyophilized samples using a Tensor 37 spectrometer (Bruker Optics, Billerica, MA), as described previously 29 . 128 scans were obtained at 4 cm −1 resolution and spectra were processed using OPUS software (v. 6.5, Bruker Optics), by cutting around 1600–1700 cm −1 , smoothing and baseline correcting before obtaining second derivative spectra.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By monitoring protein amide backbone HDX, which depends on the protein local solvent accessibility and hydrogen bonds, one can characterize the solution conformation and dynamics of proteins, including changes due to the external environment [18] (e.g., chemical modifications [19][20][21][22], buffer components [23,24], and the presence of a binding protein/ligand [25,26]). Regarding the characterization of protein aggregation, HDX-MS has shown its potential for our understanding of protein self-association interfaces and aggregation-induced protein conformational changes at the molecular level in either the lyophilized state [27] or the solution state [28][29][30].…”
mentioning
confidence: 99%